1976
DOI: 10.4319/lo.1976.21.2.0294
|View full text |Cite
|
Sign up to set email alerts
|

Uranium and thorium decay series nuclides in plankton from the Caribbean1

Abstract: Zooplankton(predominantly calanoids and cyclopoids) from the Caribbean were analyzed for 'W, 254U, 23pTh, =Th, =Ra, **'Ra, aoPb, and zloPo. The concentration factor in the zooplankton relative to seawater is highest for 210Po. "'Pb and '"Th have similar concentration factors and are comparable (when normalized to 226Ra) to reported fiberscavenging experimental data on ""Pb and %'"Th. The dominant transport agent for =OPo and ""Pb from the mixed layer to depth cannot be unmodified zooplankton debris.The abundan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
29
0
1

Year Published

1978
1978
2011
2011

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 90 publications
(33 citation statements)
references
References 12 publications
3
29
0
1
Order By: Relevance
“…Most of the 210 Pb that is bound to the cell walls is excreted with the feces. This is consistent with data reported by Shannon et al (1970), Kharkar et al (1976), Beasley et al (1978) and Heyraud and Cherry (1979), which indicated high 210 Po/ 210 Pb ratios in various plankton species. Fisher et al (1983) concluded that 210 Po/ 210 Pb ratios in fecal pellets of zooplankton are half those of their phytoplankton food supply in field samples.…”
Section: Affinity Of 210 Po and 210 Pb For Poc And Biogenic Silicasupporting
confidence: 92%
See 2 more Smart Citations
“…Most of the 210 Pb that is bound to the cell walls is excreted with the feces. This is consistent with data reported by Shannon et al (1970), Kharkar et al (1976), Beasley et al (1978) and Heyraud and Cherry (1979), which indicated high 210 Po/ 210 Pb ratios in various plankton species. Fisher et al (1983) concluded that 210 Po/ 210 Pb ratios in fecal pellets of zooplankton are half those of their phytoplankton food supply in field samples.…”
Section: Affinity Of 210 Po and 210 Pb For Poc And Biogenic Silicasupporting
confidence: 92%
“…The adsorption rate of a radionuclide is dependent on its physico-chemical behavior, its concentration in the water, the particle concentration and particle composition in the water. Kharkar et al (1976) and Heyraud et al (1976) found the following relative adsorption intensities:…”
Section: Affinity Of 210 Po and 210 Pb For Poc And Biogenic Silicamentioning
confidence: 99%
See 1 more Smart Citation
“…210 Pb and 210 Po are both particle-reactive, with varying affinities both in terms of efficiency and type of matter to which they associate and, indeed, different binding mechanisms: 210 Pb and 210 Po adsorb on particle surfaces, but 210 Po is also incorporated via biological activity and is preferentially enriched in organic tissue (Fisher et al, 1983;Kharkar et al, 1976;Shannon et al, 1970;Stewart and Fisher, 2003a&b;Stewart et al, 2005). As a consequence, 210 Po is more efficiently removed from surface waters than 210 Pb via sinking particles, and results in disequilibrium between the two radionuclides throughout the upper 500m (Figure 10 and from 40 to 60 dpm m -2 d -1 for E4 (Table 3).…”
Section: Fluxes During A4 Using 210 Po/ 210 Pbmentioning
confidence: 99%
“…234 Th and 210 Po are well known for being particle-reactive chemical property, although they may not follow the same geochemical pathway. 210 Po is more reactive with biogenic particles than other nuclides (Shannon et al, 1970;Kharkar et al, 1976;Beasley et al, 1978;Tanaka et al, 1983;Turekian et al, 1974). Shannon et al (1970) determined that the enrichment factors of 210 Po from seawater, phytoplankton and zooplankton were 1, 6 and 23, respectively.…”
Section: Introductionmentioning
confidence: 99%